Profil Penalaran Siswa SMA dalam Menyelesaikan Masalah Logika Berdasarkan Perbedaan Gaya Kognitif - Nur Aliya; Didik Hermanto; Buaddin hasan (JEMS: Jurnal Edukasi Matematika dan Sains, 2020)
This study describes high school students' reasoning profiles in solving logic problems based on impulsive and reflective cognitive styles. This research is a qualitative descriptive study. The subjects of this study consisted of one impulsive cognitive style student and one reflective cognitive style student. The supporting instruments used were the Matching Familiar Figure Test (MFFT) cognitive style test, interview guidelines, and problem-solving tasks (TPM). The data collection technique uses the problem solving task-based interview technique. Data analysis techniques using data reduction, data presentation, concluding / verification. The results showed that impulsive students solved the problem by changing the implication sentence from the question to the implication symbol, then making a truth table from the implication equivalence. Still, there were errors in writing the symbol of one of the statements. Next, the impulsive students wrote and mentioned the statement sentences obtained as a result of completion. Impulsive students provide reasons or evidence for one or several solutions by determining the second statement as an official statement and writing an example of an office sentence with universal and exponential quantor symbols. Reflective students solve problems by writing down what is known and what is asked from the questions, then underlining each statement, and marking it with a statement symbol. Then the students wrote the implication sentence with the implication symbol. Furthermore, the reflective students wrote down and mentioned the solutions obtained while circling the results obtained. With a tone of doubt, the students said the sentence "negation of implications in the form of symbols.